Reconciling Tradition and Sharia: An Evaluation of the Bejamu Saman Tradition in Aceh, Indonesia - Ripi Hamdani; M. Chalis; Nufiar Nufiar; Abdul Manan; Muji Mulia (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This article analyzes the tension between the Bejamu Saman tradition in Gayo Lues and Islamic legal norms due to the influx of modern cultural influences. The core problem lies in the practice of Najuk and the shift in artistic content that tends to emphasize sensual aspects, which harms the religious substance of tradition. The novelty of this study lies in the approach of the Sociology of Islamic Law combined with an evaluation based on Maqāṣid al-Sharī'ah to formulate a form of harmonization between local wisdom and the limitations of sharia. Using a qualitative method with a normative-juridical approach, data were collected through in-depth interviews with religious leaders, traditional leaders, and community artists in Gayo Lues Regency. The research findings indicate that Bejamu Saman is maintained as a living law because of its essential role in maintaining social solidarity and silaturahmi (ḥifẓ al-Nafs). However, the evaluation of Maqāṣid al-Syarī'ah identified a clear mafsadah in the practice of Najuk and explicit poetry that directly threatens honor (ḥifẓ al-Nasl) and ignores the principle of Sadd al-Dharī'ah. As a strategic solution, this study recommends a Cultural Reform policy to the Customary Council and the Regional Government to develop technical guidelines for preserving traditions. These recommendations include legalizing the no-touch Najuk procedure through a special forum, returning artistic content to its original form through figurative and da'wah-filled treh/sonek poetry, adjusting Bines dance movements to be less excessive, and strengthening control of performance spaces through the Keketar authority. These steps are crucial to ensure the existence of Gayo Lues culture remains in harmony with the basic values ​​of Islamic law without losing its original essence.